"Free Food on Campus!": A Novel Use of Instructional Technology to Reduce University Food Waste and Feed Hungry Students. Issue 5 (3rd September 2021) - Frank, Laura B.; Finkbinder, Emily M.; Powell, Virginia S.
ABSTRACT: Food insecurity among college students exceeds levels of household food insecurity in the United States, and is a growing problem. Simultaneously, large quantities of food are wasted on college campuses. This paper presents a simple, low-cost approach to address both issues, utilizing an electronic Learning Management System as a platform to connect college students with good quality food that would otherwise be wasted. A needs assessment, program implementation, and outcomes evaluation are described; the food rescue initiative was positively received by the campus community. This program could be easily be adopted by any educational institution that utilizes a LMS.